POTENSI GAS METHANE BATUBARA DI DAERAH KELAI, KABUPATEN BERAU, KALIMANTAN TIMUR - Sugeng Raharjo (Jurnal Ilmiah MTG, 2009)
A geological research was performed in the Berau Basin, to provide a better understanding on the potential and resources of coalbed methane (CBM) in Berau Regency, East Kalimantan Province, particularly in the Kelai Coalfield. Field observation conducted in the coalfield, shows that the banded to bright banded . Geochemical analysis shows the range of volatile matter content is from 35,17 – 40,11 %, total sulfur from 0,15 – 0,33 %, ash varies between 2,98 – 8,98 %, and fixed carbon from 39,29 – 40,34 %. Based on average of vitrinite reflectance 0,44 – 0,46 ,the coal rank of Kelai is sub-bituminous B . The Methane gas is resulted coming from biogenic process. The fairly well cleated Kelai coal shows cleat orientations trending North East – South West and perpendicular to nearly oblique to the Kelai syncline axis. An in-situ coal gas calculation tends to indicate a low to moderate methane content level, with a value of 4,40 m3/ton – 5,02 m3/t. Coal gas methane resources is 40,31 BCF.Key Words : Vitrinite reflectance, Cleat, Coalbed methane